METHODOLOGICAL PROCEDURE FOR LEARNING THE ATHLETIC DISCIPLINE – JAVELIN THROW - Simeonov, Aleksandar; Radikj, Zoran; Dejan Angelovski (My University, 2018)
For an efficient methodical procedure of the athletic disciplines it is imperative to choose a set of adequate exercises, i.e. complex of exercises to perform and master the movements that are an integral part of the structure of athletic discipline that should be mastered as a whole. The application of a good methodical procedure means when choosing the exercises to take account of their number and their interconnection. The connection requires the previous exercise to be the basis for the next and the next exercise to be an upgrade to the previous or simply said - to have a positive transfer between exercises. The order of the exercises is determined by means of a qualitative bio-mechanical analysis. The method for qualitative biomechanical analysis represents determining the biomechanical characteristics and motor stereotypes (sport elements), or to analyze the exercises for learning the athletic disciplines. This paper shows the methodological procedure for learning of the athletic discipline – javelin throw.
Keywords: javelin throw, position, methodology, exercises...